Teachers’ Experience of Contextualized English Language Teaching (Triyuga Academic Journal, 2024)
This qualitative phenomenological study was carried out to understand the lived experience of English teachers who are teaching English in different schools. The study explores the significance of a contextualized teaching approach in teaching English and the need for its application in the EFL context. Contextualized English Language Teaching (CELT) introduces language content by employing various techniques to engage students in different activities. Students who learn in a contextual environment are motivated to learn. Traditional classrooms emphasize the active role of teachers, with students remaining passive much of the time. Contextualized teaching assumes learners are creators, not merely receivers. The teacher’s main role is to create appropriate learning contexts and provide students with learning opportunities through experiences and roles. This study examines the classroom experiences of teachers teaching English in contextualized situations. The data, collected from purposively selected teachers in different schools in the Udayapur district, indicate that contextualized teaching is highly effective in developing students’ language skills.